Unveiling the tapestry of Arab American writings - Jerbi, Syrine (International Journal of Language and Literary Studies, 2023)
Arab Americans living in the United States are represented in the intriguing and varied body of Arab American Literature. It is a diverse and significant body of writing that reflects the experiences and perspectives of Arab Americans in the United States. It explores powerful examples of how difficult it is to deal with identity, heritage, and belonging concerns in a diverse community. Arab American writers, from Ameen Rihani to Naomi Shihab Nye, have made creative contributions with their viewpoints, illuminating the rich tapestry of life in Arab America in everything from provocative novels to tender poetry and perceptive essays. However, Arab American authors have faced numerous challenges, including prejudice, stereotypes, language barriers, and limited publishing opportunities. Despite these obstacles, they have persisted in using their literary works as a means of self-expression, cultural preservation, and empowerment. To promote the visibility and acknowledgment of Arab American voices, readers, institutions, and literary communities must actively support and endorse Arab American authors and their work. Arab American Literature contributes to a more inclusive and interconnected society, dispelling myths and fostering empathy and understanding across cultural divides.